Is corporate political activity an investment or agency? an application of system GMM approach - Lin, Woon Leong (MDPI, 2019)
Corporate political activity (CPA) has been recognized as bearing a significant impact on financial performance (FP). Nevertheless, there has been a lack of considerable research to date. The results of the research regarding the relationship between CPA and FP have been contradictory and this has necessitated further investigation of this relationship. Nonetheless, rather than examining the relationship between CPA and FP, research scholars have revealed that a contingency perspective must be employed for revealing the conditions and the context which enhance the relationship between these two constructs. This study offers a quite distinctive viewpoint with respect to the link between CPA and FP as regards the corporate reputation perspective. For this reason, the study obtained data from the Fortune list of top 100 World Most Admired Companies (WMAC) for the period of 2007 and 2016. This data was utilized to examine the relationship between CPA and FP using the dynamic panel data system GMM (Generalized Method of Moments) estimator. This study finds virtually no support for the hypothesis that lobbying and PACs (political action committees) represent an investment in political capital. Instead, CPA is symptomatic of agency problems within firms. This study also argues that corporate reputation moderates the effect of CPA on the FP and the analysis supports the argument. Our results are particularly useful in light of the reputable corporation, which is greatly to likely increase the use of corporate funds for political contributions.